IPO Pricing, Investor Behavior, and IPO Underpricing of High-Tech Companies: Evidence from SSE STAR Market and Nasdaq Market. (26th March 2022) - Ma, Yu; Liu, Guiling; Qi, Chaoping
Abstract : There is a significant IPO underpricing phenomenon in the stocks of high-tech companies on China Science and Technology Innovation Board (STAR Market). In order to analyze the causes of high IPO underpricing on STAR Market, from the perspective of investor behavior, this paper uses the Two-tier Stochastic Frontier Model to decompose IPO underpricing into two parts, the pricing impact of the primary market and the transaction impact of the secondary market, and then studies the differences of the impact of different markets on IPO underpricing. The results show the following: (1) the primary market pricing of most stocks, that is, the difference between the issuance price of stocks and the real value of stocks is small, which shows that the primary market pricing has a weak impact on the IPO underpricing of the STAR Market, which in turn shows that the implementation of the registration system has significantly improved the IPO pricing efficiency of the STAR Market; (2) the closing price of most stocks fell on debut, that is, the trading price of stocks is significantly higher than its real value, which shows that the blind optimism of investors in the secondary market and the irrationality of investor structure are the main factors leading to the IPO underpricing of the STAR Market; and (3) through the variance decomposition and the robustness test of grouping the industry to which the enterprise belongs, the year of listing, and issuance and the size of the enterprise, we find that in different years and different industries, the impact of investor behavior in the secondary market on IPO underpricing is significantly higher than that in the primary market. In addition, the IPO underpricing of enterprises is not affected by the size of enterprises. This shows that the behavior of investors in the secondary market has always been the main means to affect the IPO underpricing of the STAR Market. This paper expands the analysis idea of IPO underpricing, which has a certain reference significance for the reform of STAR Market and the listing and financing of scientific and technological innovation enterprises.